Երզնկայի 1230 թ. ճակատամարտը և կիլիկեցիների դիրքորոշումը - Տեր-Ղևոնդյան, Վահան («Նաիրի» հրատ.)
The creation and development of the Armenian state in Cilicia approximately coincides with the epoch of Seldjuk and Mongol domination in the Middle East (XI-XIV cc.). During that period a number of decisive battles took place each of them defining the fate of local states for some decades.
Keywords: Հայոց պատմություն